Penyuluhan Budidaya Taman Obat Keluarga ( TOGA ) di Jorong Sawah Ampang, Nagari Muaro Paneh Kec. Bukit Sundi - Fernandez, Donny; Hakiki, Syarah Nur; Febiola, Mutiara Diva; Vhannesti, Citra; Maulana, Ihsan; Siregar, Martin Rafael (Orbit: Jurnal Ilmu Multidisiplin Nusantara, 2025)
In Nagari Muaro Paneh, Bukit Sundi District, Solok Regency, West Sumatra Province, there is Jorong Sawah Ampang. The majority of people in Jorong Sawah Ampang are farmers; most people in Sawah Ampang are members of farmer groups. Although most people in Jorong Sawah Ampang are farmers, many people are not familiar with family medicinal plants, hereinafter referred to as TOGA, which have benefits as spices or cooking ingredients, but can also be used as an alternative to maintain and treat health naturally without side effects such as plants such as kencur, ginger, turmeric, and betel. Therefore, one way to preserve the cultural wisdom of medicinal plants in Nagari Muaro Paneh, especially in Jorong Sawah Ampang, is through socialization. With the socialization of this activity, the benefits and advantages of some family medicinal plants will be explained as well as how to plant and use these medicinal plants. The purpose of this community is to let people know about the benefits of traditional medicinal plants to maintain and care for health naturally without side effects, reduce expenses, or benefit the family economy by not using chemical drugs. The community knows the beneficial use of planting these plants. They also know their economic value and safety level. This is the real result of the socialization program of this activity.